2016
DOI: 10.1155/2016/4540826
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Feasibility ofMicrocystis aeruginosaas a Feedstock for Bioethanol Production under the Influence of Various Factors

Abstract: Microcystis aeruginosa, a freshwater microalga, is capable of producing and accumulating different types of sugars in its biomass which make it a good feedstock for bioethanol production. Present study aims to investigate the effect of different factors increasing growth rate and carbohydrates productivity of M. aeruginosa. MF media (modified BG11 media) and additional ingredients such as aminolevulinic acid (2 mM), lysine (2.28 mM), alanine (1 mM), and Naphthalene acetic acid (1 mM) as cytokine promoted M. ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
(31 reference statements)
0
11
1
Order By: Relevance
“…6). The highest amount of bioethanol was found 60 mM/ml, higher than the amount of bioethanol in our previous work (Khan et al 2016).
Fig.
…”
Section: Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…6). The highest amount of bioethanol was found 60 mM/ml, higher than the amount of bioethanol in our previous work (Khan et al 2016).
Fig.
…”
Section: Resultscontrasting
confidence: 58%
“…First M. aeruginosa (KMMCC-1135) was cultured in MF media under red LED light of 5000 lx with a continuous supply of 2% CO 2 (Khan et al 2016). Conical flasks (500 ml) were used for the culture of M. aeruginosa .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mata et al [ 60 ] reported that an aerated culture of microalgae under 12,000 lx intensities for 12 h of daylight produced a higher biomass yield, whereas biomass decreased when the light intensity was reduced. Khan et al [ 71 ] reported that microcystis aeruginosa give maximum biomass and carbohydrates productivity at red LED light of about 5000 lx. Daliry et al most recently reported the maximum growth rate and lipid production by Chlorella vulgaris at light intensities of 5000–7000 lx [ 72 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microcystis aeruginosa (KMMCC-1135) used in this study was obtained from the Korea Marine Microalgae Culture Center (KMMCC) and was cultured under stress conditions in MF media [33] supplemented with NaCl. When the culture attained log phase growth (OD 660 = 1), it was subjected to high temperature(35°C for one week ) and then dewatered to yield a concentrated culture (OD 660 = 1.8).…”
Section: Methodsmentioning
confidence: 99%